Salivary levels of angiopoietin‐2 in infants with infantile haemangiomas treated with and without systemic propranolol. Issue 6 (3rd April 2018) - Seamens, Alexandra; Nieman, Elizabeth; Losavio, Kristen; Bradley, Bridget; Nelson, Kate; Chen, Kuang‐Ho; Chen, Suephy; Arbiser, Jack; Lawley, Leslie P.
Abstract: Infantile haemangiomas (IHs) with functional or cosmetic concerns necessitate systemic treatment for which propranolol is the preferred treatment. However, the mechanism of action is unknown. Mouse models suggest the angiopoietin‐2 (Ang2)/Tie‐2 system is implicated. Ang2 can promote endothelial growth or induce apoptosis depending on the presence of vascular endothelial growth factor. This pilot study investigates the saliva Ang2 levels in infants with IH treated with and without systemic propranolol. Patients with clinically confirmed IHs were recruited from an academic paediatric dermatology centre. Treatment was based on clinical evaluation. Saliva samples were collected over 6 months. An enzyme‐linked immunosorbent assay determined Ang2 levels. Ang2 levels were detectable in 45% of samples. However, by the late time point, only 28% had detectable levels. There were no changes of Ang2 over time, and there were no differences in Ang2 levels between groups. However, Ang2 levels were correlated with baseline size and changes in size from baseline. Ang2 is detectable in saliva of affected infants, but does not decrease with propranolol treatment. However, Ang2 levels are positively correlated with size and changes in size. Thus, Ang2 is not the primary factor in the mechanism of propranolol resulting in IH reduction.